Pengaruh Kompensasi Dan Lingkungan Kerja Terhadap Produktivitas Kerja Karyawan Pada Perusahaan Daerah Air Minum ( PDAM ) Way Rilau Bandar Lampung - Sodirin Sodirin (Universitas Mitra Indonesia, 2020)
Abstract This study aims to examine (1) the effect of compensation on employee productivity, (2) the influence of work environment on employee work productivity and (3) the effect of compensation and work environment on employee work productivity.This research uses quantitative causality research design, research conducted at company of drinking water area way rilau bandar, research conducted by researcher in April 2017. Population in this research as many as 258 employees, to determine the number of samples by using slovin formula and got the number of samples 72 respondents.The results of beta coefficient analysis on the regression model on the compensation variable of 0.322 and large T count of 2.986 and T table of 1.66. It can be interpreted that the increase of compensation variable hence influence to the increase of work productivity. Based on result of regression test between work environment with work productivity, hence obtained coefficient of beta equal to 2,287 with value of sig 0,025 with scale of T count equal to 2,287. This can be interpreted that the improvement of the work environment affect the work productivity. Result of hypothesis testing F statistic test can be stated that compensation and work environment have a significant positive effect on employee work productivity. Keywords: Compensation, Work environment, Work productivity.